Vagus nerve stimulation: from epilepsy to the cholinergic anti‐inflammatory pathway. Issue 3 (29th January 2013) - Bonaz, B.; Picq, C.; Sinniger, V.; Mayol, J. F.; Clarençon, D.
Abstract Background The brain and the gut communicate bidirectionally through the autonomic nervous system (ANS). The vagus nerve (VN), a major component of the ANS, plays a key role in the neuro‐endocrine‐immune axis to maintain homeostasia through its afferents (through the activation of the hypothalamic pituitary adrenal axis and the central ANS) and through its efferents (i.e. the cholinergic anti‐inflammatory pathway; CAP). The CAP has an anti‐TNF effect both through the release of acetylcholine at the distal VN acting on macrophages and through the connection of the VN with the spleen through the splenic sympathetic nerve. Vagus nerve stimulation (VNS) of vagal afferents at high frequency (20–30 Hz) is used for the treatment of drug‐resistant epilepsy and depression. Low‐frequency (5 Hz) VNS of vagal efferents activates the CAP for an anti‐inflammatory effect that is as an anti‐TNF therapy in inflammatory diseases were TNF is a key cytokine as represented by experimental sepsis, postoperative ileus, burn‐induced intestinal barrier injury, colitis. However, both vagal afferents and efferents are activated by VNS. Purpose The objective of this review was to explore the following: (i) the supporting evidence for the importance of VNS in epilepsy (and depression) and its mechanisms of action, (ii) the anti‐inflammatory characteristics of the VN, (iii) the experimental evidence that VNS impact on inflammatory disorders focusing on the digestive tract, and (iv) how VNS could potentially be harnessed therapeutically in human inflammatory disorders such as inflammatory bowel diseases, irritable bowel syndrome, postoperative ileus, rheumatoid arthritis as an anti‐inflammatory therapy.